Clinical features and surgical outcomes of high grade pleomorphic xanthoastrocytomas: a single-center experience with a systematic review - Zuo, Pengcheng; Li, Tian; Sun, Tao; Wu, Wenhao; Wang, Yujin; Zhang, Mingxin; Wu, Zhen; Zhang, Junting; Zhang, Liwei (Frontiers in Oncology, 2023)
Purpose: High grade pleomorphic xanthoastrocytomas (HGPXAs) are very rare and their management and prognostic outcomes remain unclear. To better understand the disease, we aimed to evaluate the risk factors for progression-free survival (PFS) and overall survival (OS), and propose a treatment protocol based on cases from our institute and cases from the literature. Methods: The authors reviewed the clinical data of 26 patients with HGPXAs who underwent surgical treatment in Department of Neurosurgery of Beijing Tiantan Hospital between August 2014 and September 2021. We also searched the PubMed database using the keywords “anaplastic” combined with “pleomorphic xanthoastrocytoma(s)” between January 1997 and October 2022. Risk factors for PFS and OS were evaluated in the pooled cases. Results: The authors’ cohort included 11 males and 15 females with a mean age of 36.7±20.3 years (range: 5.5-71 years). Gross-total resection (GTR) and non-GTR were achieved in 17 (65.4%) and 9 (34.6%) patients, respectively. Radiotherapy and chemotherapy were administered to 22 and 20 patients, respectively. After a mean follow-up of 20.5±21.2 months (range: 0.5-78.1 months), 7 patients suffered tumor recurrence and 6 patients died with a mean OS time of 19.4±10.8 months (range: 8-36 months). In the literature between January 1997 and October 2022, 56 cases of HGPXAs were identified in 29 males and 27 females with a mean age of 29.6±19.6 years (range; 4-74 years). Among them, 24 (44.4%) patients achieved GTR. Radiotherapy and chemotherapy was administered to 31 (62%) patients and 23 (46%) patients, respectively. After a median follow-up of 31.4±35.3 months (range: 0.75-144 months), the mortality and recurrence rates were 32.5% (13/40) and 70% (28/40), respectively. Multivariate Cox regression model demonstrated that non-GTR ( p=0.015), age≥30 ( p=0.018), no RT ( p=0.007) and no CT ( p=0.042) were negative prognostic factors for PFS. Non-GTR ( p=0.001), secondary HGPXAs p=0.001), age≥30 (p=0.023) and no RT (p=0.008) were risk factors for OS. Conclusion: High grade pleomorphic xanthoastrocytomas are very rare brain tumors. Children and younger adults have better clinical outcome than elderly patients. Secondary HGPXAs had worse OS than primary HGPXAs. Complete surgical excision plus RT and CT is recommended for this entity.